Novel very small dual-band chip-size antenna for wireless sensor networks - Mendes, P. M. (2004)
We report on the design of a novel, very small dualband antenna having double-folded structure and suitable for onchip integration in wireless sensor network nodes. The antenna operates simultaneously at 2.4 GHz and 5.7 GHz with a -10 dB return-loss bandwidth of 50 MHz and 170 MHz, respectively. A prototype fabricated on a 4003 RogersTM substrate (dielectric permittivity of 3.38) has dimensions of 6x8.5 mm2.